REMOVED: Through wall human detection under small samples based on deep learning algorithm. (December 2017) - Wang, Wei; Jiang, Yu; Wang, Dan; Zhang, Min
Abstract : The Publisher regrets that this article has been temporarily removed. A replacement will appear as soon as possible in which the reason for the removal of the article will be specified, or the article will be reinstated. The full Elsevier Policy on Article Withdrawal can be found athttp://www.elsevier.com/locate/withdrawalpolicy .